Queer Masculinities in Latin American Cinema: Male Bodies and Narrative Representations - St-Georges, Charles (Imagofagia, 2021)
Sobre Subero, Gustavo. Queer Masculinities in Latin American Cinema: Male Bodies and Narrative Representations. London: I.B. Taurus, 2014, 241 pp., ISBN: 9781780763200 Resumen: reseña sobre el libro de Subero, Gustavo. Queer Masculinities in Latin American Cinema: Male Bodies and Narrative Representations. London: I.B. Taurus, 2014, 241 pp., ISBN: 9781780763200 Palabras clave: reseña, Subero, Gustavo, Queer Masculinities in Latin American Cinema: Male Bodies and Narrative Representations